The motivation in two different industries companies—manufacture and service—in Taiwan - SHEN, YI-TING (2011)
The importance of motivation has been noticed in the recent decades. It is because motivation has the function of enhancing the efficiency of the company’s operation without increase the cost. However, motivation is a complicated issue that many researchers are challenging. Since there are many factors that can influence the attitude and decision of motivation, researchers need to probe into the reasons. For example, what factors are the needs of individuals as well as what affects the individual’s decision process. Motivation is defined by many scholars and there are theories developed in order to explain individual’s behaviour. Usually, researchers examine the notion of motivation through two sorts of theories, which are content theories and process theories. The first type discussed in this research includes Maslow’s hierarchy model, Alderfer’s ERG theory, and Herzberg’s dual-factors theory. On the other hand, Vroom’s expectancy theory, Adams’ equity theory, and Locke’s goal-setting theory are in the sector of process theories. As for the culture dimension, Hofstede’s idea is utilized. These academic views are used to analyze the data collected from the questionnaire. It is concluded that the firm can group the individuals’ various perceptions and the consensus is useful in the modification of the motivation mechanism and the pattern of the motivation attitudes of the firms in research are identified.